Peningkatan Kompetensi Guru Ma’arif melalui Pelatihan Media Interaktif Google Sites di MINU al-Istiqamah - Maulidia; Haq, Rosyida Rahmatul; Khoirudin, Moch. Alfin; Amrullah, Abdul Malik Karim (Ma'arif Journal of Education, Madrasah Innovation and Aswaja Studies, 2023)
This training aims to provide knowledge and skills for madrasa teachers under the auspices of LP Ma'arif Kab. Malang in making effective and interesting interactive learning media using Google Site; This activity was held on Saturday, May 20 2023 at MINU Al Istiqomah, Malang Regency. Teachers who take part in this training are expected to be able to develop skills in designing and compiling interactive learning content that fits the needs of students and can integrate various interactive elements, such as images, videos, and external links, into the learning media they create. Participants in this activity consisted of 15 teachers who took part in training on making interactive learning media using Google Sites. Conducted in two phases, the first phase provides material on the concepts and benefits of Google Sites as a learning medium, and the second phase directly exercises creating and operating Google Sites as a medium. study. The training combines material presentation methods, hands-on practice and direct debriefing. Due to this training activity, all participants in the training were representatives of the teachers of LP Madrasah. Ma'arif Kab. Malang can understand the concepts and benefits of Google sites and can create and use them as an interactive learning medium. Recommendations for future training are to involve more participants and track the long-term effects of using interactive learning media in educational settings